Organizational Culture and Work Environment at Cosmo Amaroossa Hotel, Jakarta - Nugraha, Rizki Nurul (West Science Social and Humanities Studies, 2024)
Organizational culture and work environment are important factors that must be implemented by a company, because it can improve employee performance. The object of this research is an organization at Cosmo Amaroossa Hotel, South Jakarta, Indonesia. This type of research is qualitative, with qualitative descriptive analysis methods. Data collection was conducted by interviews and direct observation. The formulation of this research problem is how the organizational culture and work environment at Hotel Cosmo Amaroossa. The purpose of the study is to provide insight into the importance of organizational culture and work environment in the company, as well as its impact on company operations. The results showed that organizational culture at Hotel Cosmo Amaroossa, such as teamwork, focus on service quality, innovation and change, good communication, employee engagement, skills training, and involvement in the community had a significant impact on employee motivation, performance, and well-being. The working environment implemented by this hotel also makes employees more comfortable to work and creates harmonious relationships and solidarity between employees.